Epigallocatechin Gallate (EGCG) Mitigates Oxidative Stress and Restores Histological Integrity in Streptozotocin-Induced Zebrafish Model of Diabetes - Jamir, Ajungla; Longkumer, Sentiyanger; Pankaj, Prany Punj (Current Indian Science, 2024)
AimsThe primary aim of this study is to investigate the potential therapeutic effects of Epigallocatechin gallate (EGCG) in a zebrafish model of diabetes induced by streptozotocin.BackgroundDiabetes mellitus is characterized by chronic organ dysfunction and failure. Natural compounds, particularly polyphenols such as EGCG present in green tea, have garnered attention for their potential in managing various complications associated with diabetes owing to their antioxidant and anti-inflammatory properties.ObjectiveThis study seeks to evaluate the influence of EGCG on oxidative stress markers, antioxidant levels, and histopathological alterations in the liver, kidney, and gills of zebrafish rendered diabetic through streptozotocin administration.MethodsZebrafish subjects were allocated into four groups: control, diabetic, diabetic + EGCG, and control + EGCG. Superoxide dismutase (SOD) and catalase (CAT) activities were quantified, and histopathological assessments were conducted on day 21 of the experimental period.ResultsDiabetic zebrafish exhibited pronounced reductions in SOD and CAT activities relative to control counterparts, coupled with notable histological changes indicative of organ impairment. Conversely, EGCG treatment attenuated oxidative stress bolstered antioxidant defenses and mitigated histopathological abnormalities in the liver, kidney, and gills of diabetic zebrafish.ConclusionEGCG exhibits promising therapeutic potential in safeguarding multiple organs against diabetes-induced injury, underscoring its significance in ameliorating diabetic complications.OtherThese findings emphasize the importance of investigating natural compounds such as EGCG as potential therapeutic agents for managing diabetes-related complications. Further elucidation of the mechanistic underpinnings and clinical applicability of EGCG in diabetes management warrants future research endeavors.
Keywords: Zebrafish model